Fostering Digital Communities: A Case Study of a University’s Digital Master Plan Designed for Networked Learning Among Online Learners - Moy, Magdalene; Feldstein , Andrew (Proceedings of the International Conference on Networked Learning, 2024)
As online education expands, fostering digital communities that support networked learning becomes imperative. However, many universities lack comprehensive digital strategies to facilitate engagement and connections in distributed environments. This research examines the development of an inaugural digital master plan at a university where half of the student population is online. Guided by Moore’s theory of interactions (1989) and Garrison’s Community of Inquiry framework (2017), the plan aimed to enable meaningful student-to-content, student-to-instructor, and student-to-student interactions. The digital master plan was designed to provide high-level guidance on the intentional and purposeful use of the educational technologies, tools, platforms, and systems necessary for a robust online learning experience. It creates a cohesive vision and strategy for the digital learning experience, just as a campus master plan aligns the physical learning spaces. The digital master plan leverages the Community of Inquiry framework as a key reference point in its comprehensive gap analysis. The collaborative process involved multiple methods to assess gaps in the university’s infrastructure including: National Survey of Student Engagement (NSSE) data, three internal surveys, an external diagnostic analysis and plan, and audits of the learning management system’s tools and usage. Quantitative data provided insights into student perceptions, while qualitative findings explored the depth of social relationships and learning networks enabled through digital platforms. Throughout the process, the research team aimed to understand the social learning processes that support how learners develop and utilize technology to learn and foster a sense of belonging (Garrison, 2017). The process harnesses the natural motivations underpinning social network formation - namely information sharing, support seeking, and sense of belonging. Further, it operationalizes these motivations to achieve CoI’s high-order learning community goals. Analysis revealed key gaps related to: clearly defining and measuring online student success, expanding engagement opportunities in courses, leveraging technologies to facilitate connections, building a collaborative faculty culture, and improving communication. In response, the final digital master plan put forth five recommendations focused on these priority areas. Implementation and evaluation of digital platforms aligned to the recommendations indicate positive impacts on online students’ sense of connectedness, learning experience, and academic performance. This research makes important theoretical and practical contributions by developing a replicable institutional process for assessing and strategically enhancing a digital ecosystem to foster networked learning. The digital master plan provides guidance for the adoption of social technologies and pedagogies to increase community, connectivity, and collaboration. As online education continues to expand, insights from this case study can inform strategic digital planning efforts at other universities striving to overcome transactional distance and cultivate impactful virtual learning communities.